PEMETAAN WISATA KULINER HALAL DI WILAYAH PESISIR PANTAI KALIMANTAN BARAT - Riadi Budiman (Universitas Mathla’ul Anwar Banten, 2022)
West kalimantan are third largest province in Indonesia with the rich cultural make him one provincial culture. tourist destination. One of international culture festival that attracts tourists namely local and foreign Cap Go Meh in Singkawang City. Cap Go Meh is the festival legacy of the ethnic Chinese. ancestral culture. Not only the cultural festival, coastal areas the beach or areas downstream have tourist destinations in nature that is not less riveting. Visitors. Local and international visitors always present in the festival which, not only see cultural attractions any tourists will want to kind of food tasting / drinks. local local specialty. Food or drinks sold should be guaranteed halal, so that it can be enjoyed by everyone, especially Muslim consumers. Considering the number of Muslims in West Kalimantan as much as 60% of the total population. From the conditions and opportunities in the field, researchers created a website-based application using the Google Maps API database. The data source used is from LPPOM MUI Kalbar and the Youth, Sports and Tourism Office of West Kalimantan Province. The purpose of this research is to help search halal culinary tourism locations in west Kalimantan tourist areas, especially coastal areas to make it easier for tourists to find and find information about halal restaurants and help promote through digital media SMEs in West Kalimantan who have obtained halal certification and are able to present information for users to find information about halal certification on food based website applications.